Molecular and Biological Mechanisms Underlying Gender Differences in COVID-19 Severity and Mortality - Wehbe, Zena; Hammoud, Safaa Hisham; Yassine, Hadi M.; Fardoun, Manal; El-Yazbi, Ahmed F.; Eid, Ali H. (Frontiers in Immunology, 2021)
Globally, over two million people have perished due to the recent pandemic caused by SARS-CoV-2. The available epidemiological global data for SARS-CoV-2 portrays a higher rate of severity and mortality in males. Analyzing gender differences in the host mechanisms involved in SARS-CoV-2 infection and progression may offer insight into the more detrimental disease prognosis and clinical outcome in males. Therefore, we outline sexual dimorphisms which exist in particular host factors and elaborate on how they may contribute to the pronounced severity in male COVID-19 patients. This includes disparities detected in comorbidities, the ACE2 receptor, renin-angiotensin system (RAS), signaling molecules involved in SARS-CoV-2 replication, proteases which prime viral S protein, the immune response, and behavioral considerations. Moreover, we discuss sexual disparities associated with other viruses and a possible gender-dependent response to SARS-CoV-2 vaccines. By specifically highlighting these immune-endocrine processes as well as behavioral factors that differentially exist between the genders, we aim to offer a better understanding in the variations of SARS-CoV-2 pathogenicity.